2017
DOI: 10.2106/jbjs.15.00798
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes of Periacetabular Osteotomy from the Prospective ANCHOR Cohort Study

Abstract: Background: Current literature describing the periacetabular osteotomy (PAO) is mostly limited to retrospective case

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
142
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 191 publications
(158 citation statements)
references
References 41 publications
11
142
1
4
Order By: Relevance
“…The values of the minimal clinically important difference were <11 points for most of the scores evaluated in this study. This is consistent with contemporary studies on periacetabular osteotomy 12,30,31 and a classic study that described the long-term outcomes 32 . The limitations of the distribution-based approach (i.e., strong influence of the population characteristics and possible insensitivity to true differences in patient perception) dictate that future studies also use the anchoring approach.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The values of the minimal clinically important difference were <11 points for most of the scores evaluated in this study. This is consistent with contemporary studies on periacetabular osteotomy 12,30,31 and a classic study that described the long-term outcomes 32 . The limitations of the distribution-based approach (i.e., strong influence of the population characteristics and possible insensitivity to true differences in patient perception) dictate that future studies also use the anchoring approach.…”
Section: Discussionsupporting
confidence: 90%
“…It must be stressed that the overall change in health is not equal to patients' satisfaction with the surgical procedure (almost one-third of the cohort did not feel improvement in their general health, but a majority of the patients were satisfied with the surgical procedure). Importantly, the satisfaction rates were similar to those reported by other studies 12,34 . Third, since the beginning of our study, which is a part of a multicenter cohort, new patient-reported outcome measures have been developed for patients with hip problems, such as the International Hip Outcome Tool (iHOT-33) and the Copenhagen Hip and Groin Outcome Score (HAGOS) 14,35 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Within the ANCHOR group, over 1400 PAOs were performed from 2008–14 and over 1100 FAI surgeries between 2008–11 [18, 19]. Although indications for hip preservation surgery vary, pre-operative pain is the most common [12, 20, 21].…”
mentioning
confidence: 99%
“…Shelf acetabuloplasty has been reported to result in good long-term outcomes in hip dysplasia with a well-centred femoral head, a VCE angle greater than 0, and minimal osteoarthritis defined as a Tönnis grade ≤ 2 [5][6][7][8][9]. A more invasive peri-acetabular osteotomy technique has also been advocated, despite being associated with complications in up to 10.8% of patients [10].…”
Section: Introductionmentioning
confidence: 99%